2006
DOI: 10.1002/bmc.653
|View full text |Cite
|
Sign up to set email alerts
|

Determination of S‐phenylmercapturic acid in human urine using an automated sample extraction and fast liquid chromatography‐tandem mass spectrometric method

Abstract: S-phenylmercapturic acid is widely accepted as a specific biomarker for the evaluation of benzene exposure. Here, we describe a fast, specific and sensitive high-performance liquid achromatography coupled with tandem mass spectrometry (LC-MS/MS) method that has been developed and validated for the determination of S-phenylmercapturic acid in human urine. Isotope-labeled S-phenylmercapturic acid-d5 was used as internal standard to improve the method ruggedness. The fully automated solid-phase extraction method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…The levels of SPMA found were also in good agreement with those obtained using similar analytical conditions in nonoccupationally exposed subjects, which were 0.12 g/L in non-smokers and 1.31 g/L in smokers (overall range <0.05-3.33 g/L) [15], and below 0.5 g/L in non-smokers and 0.7-9.5 g/L in smokers [16]. Conversely, the SPMA concentrations reported in the present study were much lower than those reported in the above cited investigation [3], where median concentrations ranging from 4.1 g/L to 13.7 g/L were reported.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The levels of SPMA found were also in good agreement with those obtained using similar analytical conditions in nonoccupationally exposed subjects, which were 0.12 g/L in non-smokers and 1.31 g/L in smokers (overall range <0.05-3.33 g/L) [15], and below 0.5 g/L in non-smokers and 0.7-9.5 g/L in smokers [16]. Conversely, the SPMA concentrations reported in the present study were much lower than those reported in the above cited investigation [3], where median concentrations ranging from 4.1 g/L to 13.7 g/L were reported.…”
Section: Resultssupporting
confidence: 85%
“…Particularly, a CV of 10.4% for intra-day precision and 12.2% for inter-day precision, and accuracy in the range of 88-125% were reported at 0.43 g/L of SPMA by Schettgen et al [15], and withinbatch precision of 4.6% and accuracy of about 108% were reported Table 3 SPMA: within-and between-run precision and accuracy, assessed using low, medium and high level quality controls. by Li et al [16]. These better results may be due to higher linearity in the response of the instruments used, i.e.…”
Section: Sequence Id Qc (N)mentioning
confidence: 94%
“…Methods published so far for the determination of urinary mercapturic acids of benzene and toluene involve mainly LC-MS-MS [26,27,32,33,34], LC-MS [35] or GC-MS after derivatisation of the mercapturic acids with carcinogenic diazomethane [15,31]. However, most of these methods determine only one metabolite [15,23,27,28,31,32,33,35].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary 1-and 2-naphthols have previously been used as biomarkers for JP-8 exposure (Chao et al 2006;Serdar et al 2003Serdar et al , 2004. Metabolites of the aromatic compounds benzene and toluene have also been used to assess SD standard deviation, Max maximum detected concentration, Min minimum concentration or 0.07 lg/ml, LOD limit of detection (0.1 lg/ml), samples less than the LOD are coded as 0.07 lg/ml = LOD divided by the square root of 2 (see the text for a full explanation) exposure (Li et al 2006;Maestri et al 2005;Manini et al 2006;Marchese et al 2004). However, these compounds are encountered in the general environment through household products, cigarette smoke, fuels, and other products or factors outside the work environment.…”
Section: Discussionmentioning
confidence: 99%